Strategi Peningkatan UMKM Kreatif di Wilayah Terdampak Aktivitas Penambangan Nikel Melalui Pemanfaatan CSR Perusahaan Pertambangan - Hendrik Hendrik; La Sudarman (LPPM Universitas BSI, 2023)
The phenomenon of this study is mining companies' involvement in realizing responsibility for the environment, or CSR (corporate social responsibility)., is carried out through the provision of assistance, which only provides short-term problem solving in the form of rehabilitation of people's houses as well as direct assistance in the form of nine staple goods to the community. The purpose of this study is to examine strategies for increasing creative MSMEs utilization of the CSR (corporate social responsibility) program of companies engaged in nickel mining, especially MSME actors in areas affected by mining activities in Pomalaa District, Kolaka Regency. This study uses a qualitative descriptive approach that seeks to understand the various concepts found in the research process through content analysis and library research. The results of the research found that the pattern of increasing creative MSME by mining company CSR funds was carried out through partnership, community, and participatory patterns with several efforts including increasing financial capacity, increasing human resource capabilities, increasing production and technology capabilities, as well as marketing capabilities. By following the technique adopted by PT. Aneka Tambang Tbk, the Pomalaa sub-district administration can utilize this research as a guide to establish policies regarding the engagement of mining corporations in fostering the expansion of MSMEs in the Pomalaa sub-district area. The novelty of this study is to examine more deeply the strategies for increasing creative MSMEs in areas affected by mining activities with the CSR (Corporate Social Responsibility) Program.Keyword:Â Company,Â Creative,Â CSR, MSME